Pengaruh Fasilitas Kerja dan Kompetensi Terhadap Kepuasan Kerja Karyawan Pada PT. Deli Muda Perkasa Kecamatan Mersam - Kasiyati Yunita Wulansari (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
This study entitled The Effect of Work Facilities and Competence on Employee Job Satisfaction at PT. Deli Muda Perkasa, Mersam District. This study aims to determine the effect of Work Facilities and Competence on Employee Job Satisfaction. In this study, there are three variables, namely the Work Facility Variable, the Competence Variable and the Employee Job Satisfaction Variable. To answer the research objectives, the analysis was carried out using path analysis accompanied by t test and F test to see the partial and simultaneous influence of the variables studied. Based on the results of the analysis, Work Facilities and Competencies have an influence of 87.43% on Employee Job Satisfaction at PT. Deli Muda Perkasa, Mersam District. Work Facility and Competency Variables have an influence both partially and simultaneously on Job Satisfaction Variables.